Mental health history—a contributing factor for poorer outcomes in burn survivors. Issue 1 (6th April 2018) - Li, Frank; Coombs, Danielle
Abstract: Background: A pre-morbid mental health history is common in patients with severe burn injuries. This creates challenges in providing rehabilitation. The aim of this study is to cross examine the possible impact of psychological co-morbidities on outcomes. Methods: A notes audit was carried out examining patients that were admitted to Concord Hospital Burns Unit in a 3-year period (2010–2012). Patients with total body surface area (TBSA) of 20% or greater and aged between 16 and 50 years were included. Subjects were divided into a mental health group and a control group. SPSS version 21 statistic program was used for analysis the data. Results: Data collected included length of stay, time to achieve independence, %TBSA, types of burns and surgery required. Results of 69 files showed that the average length of stay per %TBSA was nearly double in the patients with a mental health problem (1.47 vs 0.88). They also had a higher rate of re-graft (52% vs 22%) due to infection and poor nutrition. The average time for patients to achieve independence in daily living activity was significantly higher ( p = 0.046) in the mental health group (36.2 days) versus the control group (24.1 days). Conclusion: Patients with a mental health history may have poorer general health. This may result in a higher failure rate of grafting, leading to a requirement of re-graft. Hence, it took a longer time to achieve independence, as well as a longer hospital stay. A mental health history in burn survivors can be a contributing factor for poorer outcomes in the adult population.